2023
DOI: 10.21203/rs.3.rs-2623397/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Total infectome of etiology and epidemiology unravels a complex infection landscape in Chinese acute diarrheal pig herds

Abstract: Background Porcine diarrhea is predominantly caused by infectious pathogens, leading to decreased appetite, poor digestion, intestinal inflammation, dysbiosis, and weight loss. These factors significantly affect productivity and performance in modern farming systems. However, the interactions between these pathogens and their temporal-spatial dynamics, as well as their interactions with other concurrent pathogens in multiorgan complex diseases, are rarely considered. Thus, understanding the relevant etiology o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…A pathogen was considered as "positive" in a sample if its abundance level was greater than 1 RPM (36). To identify potential false-positives resulting from index hopping, we used a threshold of 0.1% for pathogens present in the libraries from the same sequencing lane: any read numbers < 0.1% of the most abundant library were treated as "negative" as previously deployed (36,40). In addition, marker genes (groEL for Rickettsia, 5.8S ribosomal RNA for Tritrichomonas foetus) were mapped to conduct phylogenetic analysis for determination of evolutionary groups (see phylogenetic analysis).…”
Section: Pathogen Discovery and Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…A pathogen was considered as "positive" in a sample if its abundance level was greater than 1 RPM (36). To identify potential false-positives resulting from index hopping, we used a threshold of 0.1% for pathogens present in the libraries from the same sequencing lane: any read numbers < 0.1% of the most abundant library were treated as "negative" as previously deployed (36,40). In addition, marker genes (groEL for Rickettsia, 5.8S ribosomal RNA for Tritrichomonas foetus) were mapped to conduct phylogenetic analysis for determination of evolutionary groups (see phylogenetic analysis).…”
Section: Pathogen Discovery and Characterizationmentioning
confidence: 99%
“…Meta-transcriptomics enables the synchronous targeting of all types of microorganisms, identification of potential pathogens without prior knowledge, examination of the expressed genomic evolutionary patterns during infection, and precise identification of pathogenic co-infection dynamics and loads. This technique has been successful in revealing the entire pathogen spectrum -including viruses, bacteria, fungi, and parasites (i.e., total infectome) -in a single infection case, making it a powerful tool for modern pathogen discovery efforts (35)(36)(37)(38)(39)(40).…”
Section: Introductionmentioning
confidence: 99%
“…It can be presumed that the increased abundance of microbiota with a synergistic effect after PRRSV infection was the cause. Previous studies have suggested that correlation analysis performed on respiratory samples from immune-deficient individuals with infections provided insight into the synergistic relationship between respiratory pathogens [49]. The infection of PRRSV causes changes in animal organism functions, which may lead to secondary infections by other pathogens.…”
Section: Discussionmentioning
confidence: 99%